2013
DOI: 10.1002/anie.201300276
|View full text |Cite
|
Sign up to set email alerts
|

Monodisperse AgPd Alloy Nanoparticles and Their Superior Catalysis for the Dehydrogenation of Formic Acid

Abstract: Formic acid (FA, HCOOH) is a common small organic acid with a melting point of 8.4 8C and boiling point of 100.8 8C. It can undergo a dehydrogenation reaction, HCOOH!H 2 + CO 2 , releasing H 2 that will be important for hydrogen-based energy applications. [1] Traditionally, the dehydrogenation of FA is catalyzed by metal complexes dissolved in an organic solvent and the catalysis is enhanced by adding an additive, such as sodium formate or amine adducts. [2] To make more practical catalyst for the dehydrogena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
216
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 369 publications
(229 citation statements)
references
References 25 publications
11
216
0
2
Order By: Relevance
“…46 The influence of the type of the support material was also investigated by synthetically replacing N-SiO 2 with some of the ubiquitous support materials used in catalysis such as Influence of MnO x Nanoparticles on Poisoning Resistivity of PdAg Alloy Nanoparticles. The enhancement of Pd activity in FA dehydrogenation through Ag incorporation has already been reported for Ag@Pd 18 and PdAg 23 NPs, in which the activity increase has been attributed to a synergic effect. 47 In order to shed some light on the effect of MnO x NPs, we conducted linear sweep voltammetry (LSV), CO stripping voltammetry, and in situ FTIR analyses.…”
Section: Acs Catalysissupporting
confidence: 54%
See 1 more Smart Citation
“…46 The influence of the type of the support material was also investigated by synthetically replacing N-SiO 2 with some of the ubiquitous support materials used in catalysis such as Influence of MnO x Nanoparticles on Poisoning Resistivity of PdAg Alloy Nanoparticles. The enhancement of Pd activity in FA dehydrogenation through Ag incorporation has already been reported for Ag@Pd 18 and PdAg 23 NPs, in which the activity increase has been attributed to a synergic effect. 47 In order to shed some light on the effect of MnO x NPs, we conducted linear sweep voltammetry (LSV), CO stripping voltammetry, and in situ FTIR analyses.…”
Section: Acs Catalysissupporting
confidence: 54%
“…It is worth mentioning that quenching of the SPR bands due to alloying was also observed for oleylamine-stabilized PdAg alloy NPs. 23 The compositional analyses of the PdAg-MnO x /N-SiO 2 catalyst were also performed by detailed HAADF-STEM measurements. …”
Section: Acs Catalysismentioning
confidence: 99%
“…Xu and co-works have employed AuePd/ED-MIL-101 as a catalyst for the dehydrogenation of FA, and high activity was observed at 363 K in the presence of sodium formate [25]. Most recently, Sun and co-works have confirmed that AgPd alloy NPs supported on Ketjen carbon exhibited highly active for this reaction at 323 K [30]. However, those solid catalysts mainly composed of noble metal(s) are not suitable for large-scale practical application because of their scarcity and high cost [26].…”
Section: Introductionmentioning
confidence: 74%
“…3,6 In terms of heterogeneous catalysts, Pd is widely reported as the most active monometallic system at close to ambient conditions, and tailoring of nanoparticles' electronic properties through alloy or core-shell formation has shown dramatic promotional effects on catalytic activity. 4,7 Addition of Ag to Pd, either as the core of a core-shell particle or in an alloy has resulted in approximately a fiveand tenfold increase over Pd particles, respectively. 4,7 Tedsree et al 8 demonstrated a linear correlation between the activity of metal-core Pd-shell particles and the work function of the core metal, indicating the reaction is highly dependent on surface electron density.…”
Section: Introductionmentioning
confidence: 99%
“…4,7 Addition of Ag to Pd, either as the core of a core-shell particle or in an alloy has resulted in approximately a fiveand tenfold increase over Pd particles, respectively. 4,7 Tedsree et al 8 demonstrated a linear correlation between the activity of metal-core Pd-shell particles and the work function of the core metal, indicating the reaction is highly dependent on surface electron density. The mechanisms of the two decomposition reactions have been observed to occur through different surface bound intermediates, which have been reported to be favored on different catalytic sites.…”
Section: Introductionmentioning
confidence: 99%